Faktor–faktor penghambat dan pendukung perkembangan fisik motorik anak usia dini - Ningsih, Rizka Septia (Maliki Interdisciplinary Journal, 2025)
The importance of physical motor development in early childhood cannot be underestimated, because this aspect is crucial in shaping children’s abilities to carry out their daily activities. This study found that adequate stimulation, active parental involvement, positive parenting, and safe play facilities are key to supporting children’s physical motor development. However, this development can be hampered by a lack of stimulation, inadequate nutrition, an unsafe environment, and so on. Cooperation between family, school, and community is very important to optimize children’s motor development. Therefore, parents and educators are advised to be more active in providing motor stimulation that is appropriate to the child’s age.